1999
DOI: 10.1590/s0104-42301999000400009
|View full text |Cite
|
Sign up to set email alerts
|

Formação do cirurgião em cirurgia laparoscópica do aparelho digestivo. Experiência de 1.818 intervenções sem acidentes e sem mortalidade

Abstract: RESUMO -Desde a instalação da cirurgia laparoscópica no Hospital das Clínicas daO programa visa a formar um cirurgião com elevado nível de conhecimento capaz de atender pacientes de grande complexidade clínica, bem como realizar operações em todos os setores do tubo digestivo, incluindo as de grande porte. Com o advento da cirurgia laparoscópica, houve necessidade de estabelecer um programa para completar a formação do cirurgião do aparelho digestivo.Desde a introdução da cirurgia laparoscópica no Hospital das… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
0
4
0
5
Order By: Relevance
“…Previous studies showed high incidence of unsuspicious lithiasis in the main biliary tract (about 40% of patients with choledocholithiasis) and highlighted the conduct of routine use of intraoperative cholangiography to widen the possibility for this diagnosis; in addition, this method has other advantages, such as the study of the anatomy of the biliary tract (51,65) . On the other hand, some authors advocate that unsuspicious biliary lithiasis is infrequent, especially in individuals under 60 years of age (41,42) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed high incidence of unsuspicious lithiasis in the main biliary tract (about 40% of patients with choledocholithiasis) and highlighted the conduct of routine use of intraoperative cholangiography to widen the possibility for this diagnosis; in addition, this method has other advantages, such as the study of the anatomy of the biliary tract (51,65) . On the other hand, some authors advocate that unsuspicious biliary lithiasis is infrequent, especially in individuals under 60 years of age (41,42) .…”
Section: Discussionmentioning
confidence: 99%
“…Despite attempts in literature to use predictors to perform selective intraoperative cholangiography (20) , approximately 30% to 50% of the common bile duct stones cases present themselves in an unsuspicious manner, given the low pinpointing capacity of the commonly used tests in the preoperative evaluation of patients programmed for cholecystectomy. This emphasizes the role of routine intraoperative cholangiography as the only way to establish diagnosis in these circumstances (35,49,65) . Classically, the surgery by laparotomy for access to the main biliary tract constituted the standard treatment for choledocholithiasis, preceding choledocholithotomy and external biliary drainage (80) .…”
Section: Introductionmentioning
confidence: 99%
“…With the videosurgery entering its maturity, it is essential to maintain the stimulus for training at all levels, including undergraduate medical and not just a future residence 4 . However, with few exceptions, it is not what is happening in the majority of medical courses in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Diminuindo assim complicações relacionadas à cicatriz cirúrgica, como por exemplo, o risco de infecção (RÊGO et al, 2003). O procedimento cirúrgico é realizado pela abertura de quatro orifícios na cavidade abdominal; na região supra umbilical, região subxifóide e na região do hipocôndrio direito superior e inferior, por estes pequenos orifícios são introduzidos os trocartes utilizados no procedimento, há penetração dos mesmos até o peritônio, manipulação da víscera e do ducto e artéria cística, por tal fato a técnica estéril é imprescindível (PINOTTI et al, 1999;. É notório que o grau de trauma ou agressão cirúrgica é diretamente proporcional ao grau da resposta inflamatória pós-operatória e da imunossupressão, assim a diminuição da lesão do tecido da parede abdominal na laparoscopia contribui para vários efeitos fisiológicos benéficos, entre eles a diminuição do risco de desenvolver infecções (SABISTON JR., 2002).…”
Section: Necessidade De Integridade Tecidualunclassified
“…A técnica para realização deste tipo de cirurgia foi sistematizada com o seguimento de alguns passos previamente estabelecidos como: posicionamento do paciente na mesa operatória, acesso à cavidade peritonial efetuado através de quatro pequenas incisões para colocação de quatro trocartes, um na região supra-umbilical, outro na região subxifóide e outros dois trocartes são colocados na mesma linha, um no hipocôndrio direito e outro no epigástrio, para que haja a apreensão e dissecção da vesícula e posterior hemostasia. A operação laparoscópica necessita de um espaço para visualização e manipulação do instrumental, esse espaço é geralmente criado fazendo-se um pneumoperitônio com dióxido de carbono (CO 2 ) até atingir uma pressão de 12 a 15 mmHg, ocasionando elevação da parede abdominal e retração de órgãos sólidos como o fígado, ou de vísceras ocas, como o cólon ou o estômago no interior da cavidade (PINOTTI et al, 1999;SABISTON JR., 2002;SANTOS et al, 2001).…”
unclassified